Adherence to the World Cancer Research Fund/American Institute for Cancer Research lifestyle recommendations in colorectal cancer survivors: results of the PROFILES registry. (14th July 2016) - Winkels, Renate M.; van Lee, Linde; Beijer, Sandra; Bours, Martijn J.; van Duijnhoven, Fränzel J. B.; Geelen, Anouk; Hoedjes, Meeke; Mols, Floortje; de Vries, Jeanne; Weijenberg, Matty P.; Kampman, Ellen
Abstract: We examined adherence to the eight The World Cancer Research Foundation/American Institute for Cancer Research (WCRF/AICR) recommendations on diet, physical activity, and body weight among colorectal cancer survivors, and whether adherence was associated with intention to eat healthy and with the need for dietary advice. Adherence to these recommendations may putatively reduce the risk of recurrence and death. Studies on adherence to these recommendations in colorectal cancer (CRC) survivors are lacking. Adherence was assessed in a cross‐sectional study among 1196 CRC survivors and could range between 0 (no adherence) and 8 points (complete adherence). Participants completed questionnaires on dietary intake, physical activity, and body weight. Prevalence Ratios were calculated to assess whether adherence to recommendations were associated with dietary intentions and needs. Twelve percentage of the survivors adhered to 6 or more recommendations; 65% had a score between >4 and 6 points; 23% scored no more than 4 points. The recommendation for to be modest with consumption of meat showed lowest adherence: 8% adhered; whereas the recommendation not to use dietary supplements showed highest adherence (75%). 18% reported a need for dietary advice, but this was not associated with adherence to recommendations. Survivors with higher adherence reported less often that they had received dietary advice, were less likely to have the intention to eat healthier, but reported more often that they had changed their diet since diagnosis. There is ample room for improvement of lifestyle recommendations in virtually all CRC survivors. A minor part of CRC survivors expressed a need for dietary advice which was not associated with adherence to the recommendations. Abstract : Adherence to lifestyle recommendations on nutrition, physical activity, and body weight may putatively improve survival of colorectal cancer. This study showed that adherence to these recommendations is low among colorectal cancer survivors, with important opportunities for improvement, especially concerning the recommendations to be modest with the consumption of red meat, and to eat more plant‐based foods.